Study of Insulator to Withstand Switching Surges in Conversion Three to Six-Phase Transmission Line: Computer Simulation Analysis - Jambak, Muhammad Irfan (School of Postgraduate Studies, UTM, 2006)
Conversion of three to six-phase transmission line an alternative method to increase the present transmission line capability to meet the increasing electrical energy demand. In realizing this concept into actuality while maintaining same physical line dimensions and the same level of, the power capacity is more than 73% higher compare to three phase system. However there may exist in the conversion some impact will occur on the insulation of tower and substation equipment (considering no new items to be added) of the power system. This impact is associated with the stress due to switching phenomenon in the networks. This paper presents findings on the study of switching surges magnitudes on six-phase system by using EMTP/ATP. It was found that the magnitude of phase-to-phase switching surges of the converted system is much higher the parent system approximately 13% for phases spaced 120o and 65% for phases spaced 180 degrees.